汽提塔二次蒸汽热能利用的研究与实践 Research and practice on the utilization of secondary steam thermal energy from stripping column - 庞雪风1，王喜刚1，薛宝臣1，曲新2，韩明忱3，孙武4 PANG Xuefeng1,WANG Xigang1, XUE Baochen1,QU Xin2, HAN Mingchen3, SUN Wu4 (Zhongguo youzhi)
为节约蒸汽、降低循环水用量，以2 500 t/d大豆加工厂为例，对浸出车间汽提塔二次蒸汽热能利用进行了研究，设计将汽提塔产生的二次蒸汽与新鲜溶剂进行换热，可将新鲜溶剂的温度从52 ℃提升至56 ℃，经理论计算可节省蒸汽用量332 kg/h，节约循环水用量31.5 t/h。将该方案投入实践，发现可使新鲜溶剂的温度从51~53 ℃上升至57~59 ℃，二次蒸汽的温度降低至70 ℃左右，节约蒸汽用量2 kg/t，循环水温度降低3~4 ℃。综上，将浸出车间汽提塔二次蒸汽用于新鲜溶剂加热，可有效利用热能，提高大豆加工厂的经济效益。 In order to save steam and reduce the use of circulating water, taking a 2 500 t/d soybean processing plant as an example, the utilization of secondary steam thermal energy from stripping column in the leaching workshop was studied. By exchanging heat between the secondary steam from the stripping column and fresh solvent, the temperature of the fresh solvent increased from 52 ℃ to 56 ℃. After theoretical calculation, 332 kg/h steam and 31.5 t/h circulating water could be saved.By implementing this plan, the temperature of fresh solvent increased from 51-53 ℃ to 57-59 ℃, and the temperature of secondary steam could be reduced to about 70 ℃, saving 2 kg/t of steam and reducing the temperature of circulating water by 3-4 ℃.In conclusion, using the secondary steam from the stripping column in the leaching workshop for heating fresh solvent can effectively utilize thermal energy and improve the economic efficiency of soybean processing plant.